2016
DOI: 10.3390/toxins8100272
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Diarrhetic Shellfish Poisoning Toxin Production in Prorocentrum spp.: Physiological and Molecular Perspectives

Abstract: Diarrhetic shellfish poisoning (DSP) is a gastrointestinal disorder caused by the consumption of seafood contaminated with okadaic acid (OA) and dinophysistoxins (DTXs). OA and DTXs are potent inhibitors of protein phosphatases 2A, 1B, and 2B, which may promote cancer in the human digestive system. Their expression in dinoflagellates is strongly affected by nutritional and environmental factors. Studies have indicated that the level of these biotoxins is inversely associated with the growth of dinoflagellates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 123 publications
(226 reference statements)
1
51
0
Order By: Relevance
“…All toxigenic Prorocentrum spp. are benthic dinoflagellates (Lee et al, 2016) and rarely have been observed in higher abundances in the upper water column. This may explain the fact that the genus Prorocentrum was only detected by molecular methods and in low relative abundances (0.15% ± 0.1 average of the total reads by sample), without the presence of OA and DTX-1 in the field samples.…”
Section: Identification Of Toxigenic Species and Correspondence With mentioning
confidence: 99%
“…All toxigenic Prorocentrum spp. are benthic dinoflagellates (Lee et al, 2016) and rarely have been observed in higher abundances in the upper water column. This may explain the fact that the genus Prorocentrum was only detected by molecular methods and in low relative abundances (0.15% ± 0.1 average of the total reads by sample), without the presence of OA and DTX-1 in the field samples.…”
Section: Identification Of Toxigenic Species and Correspondence With mentioning
confidence: 99%
“…Several intensities have been reported for different dinoflagellate cultures [ 302 , 323 , 324 ]. Maximal and optimum intensity thresholds in dinoflagellate cultures seem to be species-dependent [ 325 ]. While some dinoflagellates grow better under low light intensities (e.g., 10–40 µmol photon .m −2 .s −1 ), others can effectively grow between 50–500 µmol photon .m −2 .s −1 or even more [ 47 , 268 , 324 , 325 ].…”
Section: Biotoxin and Bioactive Productionmentioning
confidence: 99%
“…CFP is the most widespread non-bacterial food poisoning associated with the consumption of tropical fish (Tester et al 2009) and impacts several islands of the Pacific Ocean (incidence rate (IR): 18,000 cases/100,000 inhabitants), Indian Ocean (IR  10,000 cases/100,000 inhabitants) and Caribbean Basin (IR: 12-500 cases/100,000 inhabitants) (Chinain et al 2014). Some benthic species of the genus Prorocentrum Ehrenberg can cause illness in humans through diarrhetic shellfish poisoning (DSP) due to the presence of okadaic acid in seafood (Tripuraneni et al 1997, Lee et al 2016. Several species of Coolia Meunier and Amphidinium et Lachmann are able to synthesize toxins which affect marine life, but the bioaccumulation of these toxins through the marine food chain has not yet been proven (Holmes et al 1995, Botana 2014, Ben-Gharbia et al 2016.…”
Section: Introductionmentioning
confidence: 99%